Bearing Performance Analysis of Anti-slip Connector. Issue 1 (June 2020) - Fang, Zhenggang; Dong, Yuming; Qi, Daokun; Zhao, Weibo
Abstract: The performance of anti-slip connector determines whether the mounted load can be reliably transmitted to the main body of transmission tower. In this paper, the specific design process for each part parameter of anti-slip connector is given, and the bearing performance of anti-slip connector is analysed by theoretical/finite element method. The results show that: The influence of the distance between rectangular steel pipes on the bearing capacity of anti-slip connector is related to the bolt grade. When the bolt grade is lower, the initial stiffness of anti-slip connector mainly depends on the rotational stiffness of two-plate connection. When the bolt grade is higher, the change of the distance between rectangular steel pipes causes the change of the linear stiffness of mounted iron bar, which leads to the obvious change of both initial stiffness and plastic bearing capacity of anti-slip connector. Meanwhile, the influence of bolt grade on the initial stiffness of anti-slip connector is also related to the distance between rectangular steel pipes. When the distance between rectangular steel pipes is smaller, the initial stiffness of anti-slip connector is greatly affected by the bolt grade. When the distance between rectangular steel pipes is larger, the initial stiffness of the anti-slip connector model is basically unchanged under the change of bolt grade. In practical engineering, when the mounted distance is limited, the corresponding bolt grade must be matched, so that the bearing capacity of anti-slip connector can be effectively performed.